STARA ZVONA IZ GOLOGORICE. - BRADARA, Tatjana (Histria Archaeologica, 2018)
This paper deals with two unknown and unpublished bells that today are found in Gologorica. One bell is the work of master Nicholaus and it was cast in 1364. The peculiarity of the other bell, the one from the 14/15 century, is an inscription i.e. dedication to St Agatha, the patron saint of bell casters, that has hitherto been recorded on Istrian bells only in literature. Other bells from Gologorica, whether preserved or mentioned in published texts, are cited here as well.